Long noncoding RNA HULC regulates the NF‐κB pathway and represents a promising prognostic biomarker in liver cancer. (10th October 2022) - Liu, Shihai; Huttad, Lakshmi; He, Guifang; He, Weitai; Liu, Changchang; Cai, Duo; Chen, Hao; Qiu, Jing
Abstract: Background: Long noncoding RNAs (lncRNAs) are involved in a diverse array of biological processes. While lncRNAs are commonly upregulated in hepatocellular carcinoma (HCC), the specific regulatory roles they play in this oncogenic context require further study and clarification. Although HULC (lncRNA highly upregulated in liver cancer) is involved in disease pathogenesis, its precise role in this context remains unclear. Methods: Here, we have explored the mechanistic relevance of HULC expression by assessing its expression in patient samples. The importance of this lncRNA in the onset and progression of HCC was investigated through in vitro approaches including Western blotting, quantitative PCR, Transwell assays, electron microscopy, wound healing assays, and real‐time cell analysis (RTCA). Additionally, the in vivo functions of this lncRNA were assessed using an orthotopic HCC xenograft in nude mouse model system. Results: HULC was identified as a lncRNA that is highly upregulated in human liver tumors. In vitro, HULC was able to promote HCC malignancy, although its excess overexpression also led robust autophagic induction, promoting the increased expression of autophagy‐associated genes including LC3 and Beclin‐1. At a mechanistic level, HULC was able to promote the phosphorylation of p65 and IkBkB thus enhancing autophagy by increasing LC3II levels in a manner dependent upon the NF‐κB pathway. HULC downregulation was also linked to impaired orthotopic HCC tumor growth in vivo . The link between HULC and autophagy may play a role in disease progression. Conclusions: These results suggest that HULC is an oncogenic lncRNA, and may thus offer value as a prognostic biomarker and promoter of HCC development, in addition to being a potential therapeutic target in this cancer type. Abstract : HULC, being oncogenic lncRNA, is a prognostic promoter of HCC.